Analisis Sistem Monitoring Geospasial SPH_AT pada Dinas Perkimtan Banyuasin - Yose Rizal (Pusat Riset dan Inovasi Nasional, 2024)
Management The management and monitoring of Surat Pengakuan Hak atas Tanah (SPHT) in Banyuasin regionfaces complex challenges, including land conflicts and limited transparency in administration. This research aims to analyse the implementation of a geospatial-based monitoring system that integrates spatial and non-spatial data to improve efficiency and spatial and non-spatial data to improve the efficiency, transparency, and accuracy of the management of SPHT. The system utilises Geographic Information System (GIS) technology to verify the location of SPHT. (GIS) technology to verify the location of land, track changes in ownership status, and generate reports on land conditions automatically. The results of the analyses show that the use of a geospatial-based system is able to accelerate the public service process, reduce the potential for land conflicts, and improve coordination between agencies. improve coordination between agencies. However, challenges such as data quality, infrastructure limitations, and human resource training needs still require further attention. Recommendations are provided to ensure successful implementation, including improving IT infrastructure, updating data, and socialising to the community. socialisation to the community.